Porous reduced graphene oxide modified electrodes for the analysis of protein aggregation. Part 1: Lysozyme aggregation at pH 2 and 7.4. (10th November 2017) - Vasilescu, Alina; Boulahneche, Samia; Chekin, Fereshteh; Gáspár, Szilveszter; Medjram, Mohamed Salah; Diagne, Abdou Aziz; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine
Graphical abstract: Highlights: Application of porous reduced graphene oxide-based electrode for protein aggregation. Part 1 identifies an electrochemical-based approach to investigate lysozyme aggregation at pH 2 and pH 7.4. Novelty lies in the exploration of prGO modified interfaces to capture different aggregation behaviors. Part 2 will be devoted to pharmaceutical samples. Abstract: Protein instability due to misfolding and aggregation is of big concern for protein based therapeutics because it impacts the bioavailability and immunogenicity of such drugs. The development of simple and cost-effective methods for the analysis of pharmaceutical formulations, indicating the presence or absence of protein aggregates, is consequently of high importance. This work proposes a novel electrochemical interface based on porous reduced graphene oxide coated glassy carbon electrode (GC/prGO) allowing for the early and sensitive identification of protein aggregation by following the change in the oxidative current of the proteins. The novelty of this work lies in the exploration of the ability of GC/prGO interfaces to capture different aggregation behaviors. Lysozyme is used as a model to follow by electrochemistry its aggregation at two pH values, pH 2 and pH 7.4, leading to the formation of amyloid and amorphous aggregates, respectively. Comparing the oxidation peak of lysozyme by differential pulse voltammetry (DPV) for different electrode architectures allowed validating the higher sensitivity of the GC/prGO interface versus bare glassy electrodes or electrodes coated with non-porous reduced graphene oxide. Parallel experiments were performed by fluorescence with thioflavin T, size exclusion chromatography and Atomic Force Microscopy (AFM) imaging. These tests further highlighted the usefulness of GC/prGO electrode to visualize in a fast and reliable manner the changes in the protein structure and the differences between the processes occurring at pH 2 and pH 7.4. In particular, the ability to emphasize changes related to the first steps in aggregation that could be indicative of the aggregation course, recommend the GC/prGO electrode in combination with DPV as a new analytical tool for aggregation studies of biopharmaceuticals. Part 2 of this work will demonstrate later the utility of this approach for the analysis of a fast acting injectable human insulin formulation, Humulin R, used for diabetes treatment as well as for calcitonin.